Teacher Self-Efficacy as a Mediator Between Formative Assessment and Self-Regulated Learning in Maldivian Primary Schools - Zidhna Waheed; Jacquline Tham; Ooi Boon Keat (Utilitas Mathematica, 2025)
Background: Formative assessment is a cornerstone of Maldivian education policy, yet its role in fostering students’ self-regulated learning (SRL) remains underexplored in this island nation. Despite its emphasis in policy, the mechanisms through which formative assessment influences SRL, particularly in primary education, require deeper investigation to inform effective teaching practices. Objective: This study investigates the mediating role of Teachers’ Self-Efficacy (TSE) in the relationship between Formative Assessment Practices (FAPR) and Students’ Self-Regulated Learning (SRL) within Maldivian government primary schools, aiming to understand how teacher practices and confidence impact student outcomes. Method: A qualitative research approach was employed, collecting data from 312 primary teachers across six regions in the Maldives. Data were analyzed using Structural Equation Modeling (SEM) to explore the relationships between FAPR, TSE, and SRL, ensuring robust statistical insights into the mediating dynamics. Results: Findings reveal that formative assessment practices significantly enhance SRL in students. Teachers who consistently implement FAPR exhibit higher self-efficacy, indicating that these practices bolster teacher confidence. However, TSE does not directly influence SRL; rather, it acts as a partial mediator, amplifying the positive effect of formative assessment on SRL development. Conclusions: The study highlights the critical link between formative assessment and SRL, emphasizing the need to integrate these practices into Maldivian education policies. Professional development programs should focus on enhancing teachers’ self-efficacy to optimize formative assessment strategies. To address potential biases from self-reported data, future research should incorporate observational or experimental methods. These insights offer a pathway to improve teacher practices and student academic growth by embedding formative assessment effectively within the Maldivian education system.